A Novel Predictive Control Algorithm For Autonomous Power Supply Systems; ACM International Conference Proceeding Series; 4th International Conference on Frontiers of Educational Technologies (ICFET 2018) - Garganeev A. G. Alexander Georgievich (Chapter VII-Power Engineering and Energy, 2018)
Title screen